2009
DOI: 10.1007/s10681-009-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Difference in response to drought stress among Tibet wild barley genotypes

Abstract: Wild barley germplasms are a treasure trove of useful genes and provide rich sources of genetic variation for crop improvement. We carried out a hydroponic and pot evaluation of diverse germplasms in response to drought stress using 47 Tibet annual wild barley genotypes. Our results from the hydroponic experiment showed that SPAD (soilplant analyses development analyses, based on chlorophyll meter readings), plant height, and biomass of shoot/root were significantly reduced in plants exposed to drought stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
89
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 17 publications
10
89
0
Order By: Relevance
“…Limited biomass production under drought stress was detected in a lot of studies in barley in field experiments [41], greenhouse experiments [13,45] and hydroponics [14], and was also observed in different developmental stages [46]. In our studies, a significant effect of the treatments and genotypes and also significant interactions of genotypes and treatments were detected (Table 2), which are due to the large variability of the 156 genotypes analysed, and makes this set highly suitable for GWAS.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Limited biomass production under drought stress was detected in a lot of studies in barley in field experiments [41], greenhouse experiments [13,45] and hydroponics [14], and was also observed in different developmental stages [46]. In our studies, a significant effect of the treatments and genotypes and also significant interactions of genotypes and treatments were detected (Table 2), which are due to the large variability of the 156 genotypes analysed, and makes this set highly suitable for GWAS.…”
Section: Discussionsupporting
confidence: 65%
“…The actual amount of absorbed water, i.e., total leaf water (LW), can be measured by comparing fresh weight (FW) and dry weight (DW) of above ground biomass at a defined time point [13,14]. Other parameters are the leaf water content (WC), which is estimated in relation to dry weight, or the relative water content (RWC), based on the full turgid weight of leaves [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that wild barley contained special germplasm with high tolerance to abiotic stresses, such as salinity and drought (Zhao et al, 2010;Wu et al, 2011). The current study showed that Tibetan wild barleys have wide genetic variation in BAA and BAT.…”
Section: Discussionmentioning
confidence: 55%
“…Wild relatives of major crops could be a starting point [70], although they have not been used extensively in conventional breeding. Drought tolerance has been identified in wild emmer (Triticum dicoccoides) [71], certain barley genotypes from Tibet [72], wild Oryza spp. and accessions of cultivated rice [73], and pearl millet (Pennisetum glaucum) [74].…”
Section: Discussionmentioning
confidence: 99%